A STUDY ON DISTRIBUTED LEADERSHIP PRACTICES AND ITS IMPACT ON TEACHING AND LEARNING - Kumari, H M Lalitha (PUPIL: International Journal of Teaching, Education and Learning, 2021)
School leadership has become very popular in the current educational discourse. Distributed leadership has been identified as one of the most important leadership practices in terms of enhancing the quality of teaching and learning since it involves many members of the school. Also, it has been found that the main purpose of distributed leadership is to create secondary level leaders within the school and thus give more opportunities for teachers to improve their leadership skills. This study focused on investigating the distributed leadership practices and their impact on teaching and learning in type 1C and type 2 schools in Sri Lanka. The objectives of this study were to identify how principals and teachers understand the concept of distributed leadership; how distributed leadership practices enhance teaching and learning; and what challenges principals and teachers face when devolving and practicing leadership responsibilities in their schools. Altogether 8 schools, 8 principals, 10 sectional heads, and 200 teachers were selected for the study. Both questionnaires and semi-structured interviews were used to gather the data necessary. The findings revealed that all the principals and a significant number of teachers in the type 1C and type two schools fully understood the concept of distributed leadership and have linked it with teaching and learning. The study further revealed that the distributed leadership practices contributed to enhancing the quality of teaching and learning in both types’ schools to some level. However, it was revealed from this study that a significant number of teachers and principals in both types’ schools face a number of challenges when practicing distributed leadership roles in their schools due to the major challenge of not having a collaborative working environment.